Understanding the Death of Massive Stars Using an Astrophysical Transients Observatory - Roming, Peter W. A.; Baron, Eddie; Bayless, Amanda J.; Bromm, Volker; Brown, Peter J.; Davis, Michael W.; Fialkov, Anastasia; Fleming, Brian; France, Kevin; Fryer, Chris L.; Greathouse, Thomas K.; Hancock, Jed J.; et al. (Frontiers in Astronomy and Space Sciences, 2018)
The death of massive stars, manifested as gamma-ray bursts and core-collapse supernovae, critically influence how the universe formed and evolves. Despite their fundamental importance, our understanding of these enigmatic objects is severely limited. We have performed a concept study of an Astrophysical Transient Observatory (ATO) that will rapidly facilitate an expansion of our understanding of these objects. ATO combines a very wide-field X-ray telescope, a near-infrared telescope, a multi-mode ultraviolet instrument, and a rapidly slewing spacecraft to realize two primary goals: 1) characterize the highest-redshift massive stars and their environments, and 2) constrain the poorly understood explosion mechanism of massive stars. The goals are met by observing the first massive stars to explode as gamma-ray bursts and to probe their environments, and by observing the shock breakout of core-collapse supernovae to measure the outer envelope parameters of massive stars. Additionally ATO will observe the shock breakout of Type Ia supernovae and their shock interaction with a companion, electromagnetic counterparts to gravitational wave sources, tidal disruption events, cataclysmic variables, X-ray transients, flares from exoplanet host stars, and the escape of ionizing radiation from star-forming galaxies. A description of the ATO instruments, the mission simulation, and technology readiness level is provided.